Diabetes Mellitus Prevalence and Burden among Community Acquired Pneumonia Patients - Reda Abdel Latif Ibrahem; Mostafa El Najjar; Mohamed Abdel Raouf Korani (Intelektual Pustaka Media Utama, 2018)
This work aimed at measuring the prevalence of Diabetes Mellitus among community acquired pneumonia (CAP) patients and declaring its effect on CAP patient's outcome. Both community acquired pneumonia and diabetes mellitus are common in Egypt, and patients with associated CAP and DM need special care and supervision. This prospective study was carried out on 108 CAP patients admitted to Abassia Chest Hospital during the period from January 2016 to December 2016. Clinical and radiological diagnosis of pneumonia and DM diagnosis were performed. DM recorded a prevalence of 39.8% among community acquired pneumonia patients. Disturbed level of consciousness is more frequent among diabetic patients than non diabetics. Diabetic patients recorded higher rate of hospital admission, longer duration of hospital stay, higher rate of ICU admission and more sever pneumonia than among non diabetic patients. CURB-65 score showed significant positive correlation with HbA1c of the patients. Associated community-acquired pneumonia and diabetes mellitus is frequent in our locality and labor a double burden on the affected patients leading to poorer prognosis, higher rate of hospitalization with longer duration of hospital stay and ICU admission. So CAP patients with DM need intimate care.